Numerical solution of a critical Sobolev exponent problem with weight on 𝕊3. Issue 1 (1st January 2021) - Almarashi, Adel; Mechai, Idir; Msmali, Ahmed; Yazidi, Habib
Abstract : In this paper, we prove the existence of a positive solution for elliptic nonlinear partial differential equation with weight involving a critical exponent of Sobolev imbedding on S 3 . Moreover, we discuss numerically the influence of the weight on the radius of the domain for which the given PDE has a positive solution.